High-resolution 2D seismic imaging and forward modeling of a polymetallic sulfide deposit at Garpenberg, central Sweden - Ahmadi, O.; Juhlin, Christopher; Malehmir, A.; Munck, M. (2013)
We acquired a high-resolution 2D seismic profile to test the capability of the seismic method in imaging a sulfide ore body at Garpenberg, central Sweden. Delineation of the geologic structures, which surround and host the ore body, is another goal of the survey. Due to the 3D geology of the structures, a cross-dip correction performed to image out-of-the-plane reflections, resulting in a clear high amplitude anomaly at a time and location to that to be expected from near the top of the ore body. Furthermore, DMO processing and migration are applied to the data, providing images of four main reflection groups. The reflections have been interpreted as corresponding to geologic rock units in the area that partly interfere with the potential ore body signal. To further investigate the seismic response of the ore body, forward modeling by ray-tracing is applied using the ore body geometry as mapped by drilling. We use two ray-tracing approaches: standard 3D ray-tracing and an exploding reflector approach. Seven representative samples from the mine area are used to determine P-wave velocities. The measurements show a considerable contrast between the ore body and host rock. By comparing the modeled and observed data, we find that the high amplitude signal in the real seismic section most likely emanates from near the top of one concentrated ore which lies inside the larger mapped ore body that has been modeled as a resource. The base of the ore body is only observed on the synthetic data whereas a signal penetration analysis suggests that the seismic signal penetrated efficiently along the entire survey line. Presence of disseminated ore and lower fold toward the northern end of the profile could be combined reasons that make imaging the base of the ore body difficult.